Avaliação da aprendizagem e deficiência intelectual na perspectiva de professores do ensino comum - Valentim, Fernanda Oscar Dourado; Oliveira, Anna Augusta Sampaio de [UNESP] (My University, 2013)
The aim of this study was to identify and analyze the conceptions of a group of teachers in cycle-1 elementary school on intellectual disability and assessment of school learning. It is a qualitative research that used a semi-structured interview script for its investigation. The teachers' reports showed some weakness and lack of preparation to deal with the inclusion of pupils with intellectual disabilities, and consequently difficult to assess their learning conditions. It was also found that the assessment used by them was characterized by sluggish and it was based mainly on the use of quantitative measuring instruments. Such instruments shortly guide the process of teaching and learning, consequently do not contribute to effective the inclusion of these school students.

O objetivo deste estudo é identificar e analisar as concepções de um grupo de professores do Ensino Fundamental (ciclo I) sobre deficiência intelectual e avaliação da aprendizagem escolar. Trata-se de uma pesquisa de cunho qualitativo que utilizou para investigação um roteiro de entrevista semiestruturado. Os relatos dos professores demonstraram certa fragilidade e despreparo para lidar com a inclusão escolar dos alunos com deficiência intelectual e, consequentemente, dificuldade de avaliar suas condições de aprendizagem. Verificou-se ainda que a avaliação utilizada por eles caracteriza-se por ser pouco dinâmica e baseia-se, essencialmente, na utilização de instrumentos quantitativos e de mensuração, que pouco orientam o processo de ensino e aprendizagem e, dessa forma, não contribuem para a efetivação da inclusão escolar desses alunos.
Evaluation of learning and intellectual disability in the perspective of teachers in the common teaching
Keywords: deficiencia intelectual; avaliação pedagógica; concepção de professores